Phenazine biosynthesis-like domain-containing protein (PBLD) and Cedrelone promote antiviral immune response by activating NF-ĸB - Peili Hou; Hongchao Zhu; Fengyun Chu; Yan Gao; Xiaonan Sun; Fuzhen Zhang; Xiaomeng Wang; Yueyue Feng; Xingyu Li; Yu Liu; Jun Wang; Xiaoyun Wang; et al. (Nature Communications)
Abstract Phenazine biosynthesis-like domain-containing protein (PBLD) and Cedrelone have been identified as tumor suppressors. However, their roles in virus infection remain unclear. Here, we demonstrate that PBLD upregulates the type I interferon (IFN-I) response through activating NF-kappaB (NF-κB) signaling pathway to resist viral infection in cells and mice. Mechanistically, PBLD activates NF-κB signaling pathway during viral infection via blocking tripartite motif containing 21 (TRIM21)-mediated phosphorylated inhibitory kappa B kinase beta (IKKβ) degradation. Furthermore, we show Cedrelone inhibits viral replication by increasing the PBLD protein expression and subsequently activating NF-κB-mediated IFN-I response. Furthermore, the therapeutic potential of Cedrelone lies in its ability to enhance antiviral immunity in primary macrophages and to promote survival and reduce lung tissue damage in HSV-1-infected mice in a PBLD-dependent manner. Consequently, our findings provide a potential combination model that targets PBLD for Cedrelone antiviral drug therapy, potentially paving the way for the development of broad-spectrum antiviral agents.